State of Empowerment Low-Income Families and the New Welfare State - Barnes, Carolyn (University of Michigan Press, 2020)
On weekday afternoons, dismissal bells signal not just the end of the school day but also the beginning of another important activity: the federally funded after-school programs that offer tutoring, homework help, and basic supervision to millions of American children. Nearly one in four low-income families enroll a child in an after-school program. Beyond sharpening students' math and reading skills, these programs also have a profound impact on parents. In a surprising turn-especially given the long history of social policies that leave recipients feeling policed, distrusted, and alienated-government-funded after-school programs have quietly become powerful forces for political and civic engagement by shifting power away from bureaucrats and putting it back into the hands of parents. In State of Empowerment Carolyn Barnes uses ethnographic accounts of three organizations to reveal how interacting with government-funded after-school programs can enhance the civic and political lives of low-income citizens.